PENURUNAN STUNTING MELALUI POLA ASUH DAN BERAS FORTIFIKASI PADA BALITA DI MEMPAWAH - Tarigan, Gita Handayani; Pou, Rudy; Ningrum, Nathalia; Fadhilah, Dzikri (Universitas Trisakti, 2024)
This PKM is the Corporate Social Responsibility (CSR) Bulog Nutrition Program which aims to reduce stunting through increasing family capacity, increasing the capacity of mothers under five and pregnant women in terms of parenting patterns and nutritional fulfillment, as well as increasing the capacity of posyandu cadres in terms of examining, recording and reporting nutritional status. toddlers in the work area. There were 41 toddlers and 32 pregnant women with malnutrition and at risk who were targeted. All toddlers and pregnant women meet the target criteria of CSR, in terms of family socio-economic criteria and weight/height criteria, and history of disease dan nutritional status. Activities were carried out in two stages, implementation and evaluation (after 3 months). In the first phase, anthropometric tools were provided along with training to posyandu cadres regarding procedures for measuring the height and weight of toddlers, also providing material regarding Clean and Healthy Living Behavior (PHBS) and Family Nutrition, assessing the nutritional and health status of toddlers and pregnant women, conducting demonstrations cooking healthy food for toddlers, providing fortified rice for the target to consume for 3 months. The results showed an increase in maternal parenting patterns by seeing an increase in the frequency of eating >3 times a day (85.4%), an increase in the frequency of making varied meals (48.8%), feeding children regularly (75.6%), as well as an increase in the nutritional status of all targets who received the intervention. From the changes above, it can be concluded that the Bulog Nutrition program has gave a positive impact on targets.